Compound heterozygous variations in IARS1 cause recurrent liver failure and growth retardation in a Chinese patient: a case report - Ting-Ting Zou; Hua-Qin Sun; Yu Zhu; Tian-Tian He; Wen-Wu Ling; Hong-Mei Zhu; Zi-Yuan Lin; Yan-Yan Liu; Shan-Ling Liu; He Wang; Xue-Mei Zhang (BMC, 2022)
Abstract Background Aminoacyl-tRNA synthetases (ARSs) are enzymes responsible for attaching amino acids to tRNA, which enables protein synthesis. Mutations in isoleucyl-tRNA synthetase (IARS1) have recently been reported to be a genetic cause for growth retardation, intellectual disability, muscular hypotonia, and infantile hepatopathy (GRIDHH). Case presentation In this study, we reported an additional case of compound heterozygous missense variations c.701 T > C (p.L234P) and c.1555C > T (p.R519C) in IARS1, which were identified using medical exome sequencing; c.701 T > C (p.L234P) was a novel variant, and c.1555C > T (p.R519C) was found in GnomAD. Unlike other reported patients, this individual presented prominently with recurrent liver failure, which led to her death at an early age of 19 months. She also had significant growth retardation, muscular hypotonia, chubby and flabby face, recurrent loose stools, and abnormal brain computed tomography (CT), while zinc deficiency and hearing loss were not present. Studies in zebrafish embryo modeling recapitulated some of the key phenotypic traits in embryo development, neurodevelopment, liver development, and myogenesis, demonstrating that these variations caused a loss of gene function in IARS1. Conclusions We have found a novel mutation point c.701 T > C (p.L234P) in IARS1. Compound heterozygous mutations of c.701 T > C (p.L234P) and c.1555C > T (p.R519C) in IARS1 are pathogenic, which can cause GRIDHH in child.